2017
DOI: 10.1080/21691401.2017.1416391
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of conjunctiva mesenchymal stem cells into secreting islet beta cells on plasma treated electrospun nanofibrous scaffold

Abstract: Transplantation of stem cells using biocompatible nanofibrous scaffolds is a promising therapeutic method for treating Diabetic Mellitus. The aim of this study was to derive insulin-producing cells (IPCs) from conjunctiva-derived mesenchymal stem cell (CJMSCs) and to compare the functionality of differentiated IPCs in a three-dimensional (3D) culture with 2D. Furthermore, the effects of hydrophobicity of scaffold on IPCs differentiation were examined. Scanning electron microscopy (SEM), quantitative real times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…Previous studies have shown that 3 D cultures increase global gene expression, cell differentiation and cell proliferation. It has been stated that in 3 D culture, these cellular behavior may be related to physiological interactions of cultured cells with neighboring cells and extracellular matrix [28][29][30][31][32]. Besides the increase in the expression of genes in mRNA and protein level which are determinant in differentiation of IPCs and production of insulin in 3 D culture (as shown here), Baharvand et al have shown that the involvement of cellular organelles in protein synthesis also increase [33].…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have shown that 3 D cultures increase global gene expression, cell differentiation and cell proliferation. It has been stated that in 3 D culture, these cellular behavior may be related to physiological interactions of cultured cells with neighboring cells and extracellular matrix [28][29][30][31][32]. Besides the increase in the expression of genes in mRNA and protein level which are determinant in differentiation of IPCs and production of insulin in 3 D culture (as shown here), Baharvand et al have shown that the involvement of cellular organelles in protein synthesis also increase [33].…”
Section: Discussionsupporting
confidence: 60%
“…The result of this study showed expression of these factors was higher in cells cultured on PES nanofibrous scaffold compared to those cultured as two-dimensional in tissue culture plates. Different studies showed that in the PES scaffolds microenvironment, global gene expression, differentiation and proliferation increased [17,[26][27][28]. Furthermore, in this circumstance, cellular behaviour altered due to cellular interactions to neighbouring cells and extracellular matrix [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…97 The spun fibers offer the possibility of fabricating scaffolds with a high surface to volume ratio, adaptable porosity properties, and applicability for a broad spectrum of materials. 97,98 Researchers used this relatively simple technique to produce polymer fibers from PLA, 99101 PVA, 53,99,100,102 PCL, 53,96,103,104 polyglecaprone (PGC), 96 PEOT/PBT, 90 gelatin, 105 polyethersulfone, 106,107 silk fibroin, and collagen. One disadvantage of this fabrication method might be the difficulty of scaling up these scaffolds to allow therapeutic human dosages.…”
Section: Resultsmentioning
confidence: 99%